Characterization of Porosity and Copper Infiltration Mechanism in Sintered Steel via Computed Tomography - Pengcheng Lin; Linshan Wang; Shuanghua Liang; Xuebing Liang; Qiang Hu; Limin Wang; Xuanhui Qu (Metals)
This study employs CT non-destructive detection to quantitatively analyze the pore structure of sintered steel and investigate copper infiltration mechanisms. As density increases from 6.55 to 6.95 g/cm3, pore characteristics exhibit significant changes: pore quantity initially increases then decreases, while average pore size monotonically reduces from 35.7 to 17.2 μm. Copper infiltration dramatically transforms the material’s porosity, characterized by reduced pore count, decreased distribution uniformity, increased closed pore proportion, and morphological regularization. The infiltration process demonstrates selective filling, primarily governed by pore connectivity, size effect, and capillary forces. Molten copper preferentially penetrates high-connectivity networks, prioritizing irregular angular regions. Medium-sized pores (10.52–23.76 μm) with optimal connectivity are predominantly filled. At 6.75 g/cm3, an optimal balance between pore quantity, size, and connectivity facilitates uniform copper infiltration.